(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The study aimed at knowing the financial consumer about the available protection from financial and banking services, presenting, and examining the evidence of some indicators indicating the reality of financial inclusion in the Iraqi banking system. Therefore, the study sought to know the extent of the level of protection available to the financial consumer as a result of its use of financial and banking services by the Iraqi banking system, and what It is the reality of financial inclusion in the banking system by measuring some financial and banking indicators. The study relies on the two (analytical) and (descriptive) approaches based on the questionnaire form and the data issued by the Central Bank of Iraq (2017-2020). Watching those who are knowledgeable and familiar with the Iraqi banking system, to show the relationship between the study variables, and after analyzing and studying these data, the research came out with a set of conclusions, including that protecting the financial consumer has become a requirement for legislation and tightening control procedures to ensure the rights of the financial consumer. Legislation related to financial consumer protection and review of consumer instructions, controls and processes Financial by the regulatory authorities to keep abreast of developments in the banking environment, in cooperation with international regulatory bodies.